Automotive suspension & steering systems : - Schnubel, Mark (Cengage Learning, 2015)
This edition now offers opportunities to explore the latest advancements in suspension and steering technology, including: run-flat tires, shock absorber mountings on SUVs, the effect of 42V electrical systems on power steering pumps, electronic power and four-wheel steering systems, and new wheel alignment procedures